Central fatigue - Gandevia, S. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The term `central` fatigue recognises that some important processes and limitations accompanying different types of human physical activity reside in the central nervous system (CNS). Furthermore, some of these processes lead to suboptimal force output from muscles in maximal voluntary tasks and hence it is important to determine the underlying mechanisms. The definition of central fatigue is a progressive exercise-induced failure of voluntary activation of the muscle. A subset of this type of fatigue is `supraspinal` fatigue which refers to failure to generate output from the motor cortex. For reviews of the development of these concepts see Gandevia (2001), Taylor & Gandevia (2008) and Enoka & Duchateau (2008). The latter type of fatigue can be quantified with transcranial magnetic stimulation of the motor cortex. In terms of impaired force capacity, the development of supraspinal fatigue has been documented for both upper and lower limb muscles. It arises not only with isometric contractions but also with rhythmic exercise such as cycling. It can represent a large fraction of force loss in a maximal effort. Many factors are involved in the development of central fatigue. Muscle contraction alters the sensory input reaching the spinal cord and supraspinal sites. There are resultant changes in the drive to the motor cortex in sustained efforts as revealed by studies using electromagnetic stimulation and neuroimaging. Changes also occur in motor cortical circuits. In addition to changes in spinal reflexes, recent work using corticospinal stimulation (at a subcortical location) shows that exercise can profoundly depress motoneuronal responses to descending excitatory inputs (e.g. Butler et al. (2003); McNeil et al. (2009). Ultimately, with exercise, the CNS must overcome many fatigue and activity-dependent processes occurring at different levels of the neuraxis and it must adapt its output to cope with changes in the size and dynamics of muscle force production.